The Implementation of Tongue Twister Method to Improve Students’ English Pronunciation - Hamzah Haz; Nurul Imansari; Nurhaeni Nurhaeni (Universitas Khairun, 2022)
This study aims to determine the effectiveness of the use of the tongue twister method on students' pronunciation. This research employed quantitative research with a quasi-experimental design. The population of this study is the second-grade students of SMAN 1 Campalagian, 150 students, and the sample consists of 32 students who are divided into two groups; the control group (16 students) and the experimental group (16 students). The control group was taught using the song technique while the experimental group was taught using the tongue twister method. The researchers used test (Pre-test and post-test) as the instrument in the study. Based on the test results, the researchers conclude that the average post-test score is higher than the pre-test, those are (60>55) and (75>65). This research indicates that there is a significant difference in value between the two. Therefore, it can be concluded that students make improvement in learning pronunciation through tongue twisters.